Readiness of Kindergarten Teachers for Inclusive Education - Nesyna, Svetlana; Starovoit, Nataliya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to study psychological and professional readiness of kindergarten teachers for inclusive education. 44 kindergarten teachers from Kaliningrad and region were included in the sample. A questionnaire was applied as a data-gathering tool. According to the results, kindergarten teachers accept the idea of inclusive education positively and expect that it is the children with special needs who would receive the biggest benefit. At the same time, realization of the idea of inclusive education causes anxiety and fears, associated with complexity of pedagogical activity, children interaction, necessity of special conditions for successful inclusion. Most kindergarten teachers don’t have professional and educational experience for interaction with children who have special needs. Moreover it has been revealed deficiency of psychological and professional readiness for inclusive education in the groups of kindergarten teachers. Successful realization of inclusion requires additional professional training and development of system of pedagogical and psychological support for kindergarten teachers.